The Influence of Social Media Platforms and Advertisements on Consumer Purchasing Behavior: A Study of Demographic Variations in Nepalese Youth - Chaudhary, Huma Kumari (NPRC Journal of Multidisciplinary Research, 2024)
Background: The growing influence of social media platforms on consumer behavior, particularly in developing countries like Nepal, has been a subject of increasing interest. As social media usage rises, the impact of advertisements on purchasing decisions becomes a critical area of exploration, especially among the youth. This study seeks to understand how demographic factors, including age and gender, affect social media usage patterns and the influence of advertisements on purchasing behaviors.Objective: The primary objective of this research is to examine the relationship between social media usage and consumer purchasing decisions, with a focus on the demographic characteristics of age and gender among Nepalese youth.Methods: A cross-sectional survey was conducted with 123 respondents from different age groups, ranging from 16 to above 35 years. Descriptive data analysis was employed to assess demographic distributions and social media usage patterns, while a Chi-Square test was used to analyze the influence of gender on purchasing behavior due to social media advertisements. Respondents were asked about their preferred social media platforms, purchasing behaviors, and their views on the influence of social media advertisements.Findings: The results revealed that Instagram is the most popular social media platform across all age groups, with a notable gender difference in platform preferences. Social media advertisements were found to influence purchasing behavior, with a majority of respondents either agreeing or being uncertain about their impact. The Chi-Square test showed no significant relationship between gender and the influence of social media advertisements on purchasing decisions. The majority of participants, particularly those aged 16-25, indicated that they were influenced by social media ads in their purchasing choices.Conclusion: This study highlights the substantial impact of social media advertisements on the purchasing decisions of Nepalese youth, particularly among those aged 16-25. Gender did not appear to significantly influence the effectiveness of these advertisements. The findings suggest that social media platforms, especially Instagram and Facebook, play a crucial role in shaping consumer behavior, and advertisers should focus on these platforms to target younger audiences.Novelty: This study provides valuable insights into the specific impact of social media advertisements on consumer behavior in Nepal, a developing market, and explores the role of demographic factors in shaping these behaviors.